DEVELOPMENT OF BUSINESS ACTIVITIES OF AGRICULTURAL ENTERPRISES UNDER THE CONDITIONS OF DYNAMIC BUSINESS CLIMATE - Богачик, П. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
For the formation of competitive strategies of agricultural enterprises it is necessary to carry out a thorough analysis of the market business climate under conditions of rapid growth of the production and sales leading to the market overstocking. The analysis of the business climate of commodity markets of cereals; legumes and oilseeds; as well as consumer markets for finished products allows us to follow better the current market trends. Based on the analysis; in the article the author suggests the use of multi-strategies which will significantly increase the level of competitiveness of agricultural enterprises. Increasing the profitability of domestic agricultural enterprises will provide additional tax revenues to local budgets and create conditions for the preservation of highly qualified specialists in rural areas. The result of scientific studies is proposals for increasing the efficiency of entrepreneurial activity of enterprises under the conditions of market imbalance. Under the conditions of the rapid development of markets; a very important task is econometric studies to optimize the redirection of cereal; legume and oilseed crops. This will allow increasing profitability of entrepreneurial activities of agricultural enterprises and maximize profits.